Discursive Formulas Derived from Propositional Predicates - E. R. Ioanesyan (Научный диалог)
The study is in line with the work on discursive formulas — multiword idiomatic remarks in response to the words of the interlocutor. Discursive formulas based on propositional predicates on the material of several languages, are considered. Discursive formulas of agreement and confirmation, disagreement and denial, surprise are presented as the object of description. The importance and relevance of studying discursive formulas is determined by the fact that they play an important role in the processes of oral communication, and also by the fact that these units are to a large extent linguistically specific. The novelty of the study is determined by the fact that in the work on the material of several languages, analogies and differences in the structure of the considered discursive formulas of different languages, linguistically specific formulas are considered. Two types of differences in the structure of discursive formulas in different languages have been revealed: 1. The same meaning in different languages is expressed by expressions that are different in their internal form. 2. Discursives in different languages, similar in their internal form, differ in their meanings. The study of discursive expressions in different languages is essential for semantic typology.